Diplomasi Indonesia dalam Membangun Interfaith Harmony melalui ASEM Interfaith Dialogue (2004-2009) - Renaldo Benarrivo (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2016)
Indonesia utilize interfaith dialogue as a feature of its diplomacy. This is done because of a misperception of the international community toward the Muslim faith. Islamic value used as justification for some acts of terrorism, so that Indonesia as a country with a majority Muslim population felt compelled to undertake in response to the views of the international community. ASEM becomes one of the forums utilized by Indonesia's diplomacy in particular through interfaith dialogue. This study uses qualitative research with descriptive type in describing Indonesia's diplomacy. Indonesia has a significant role in any organization of ASEM Interfaith Dialogue, both as host and as a co-sponsor. Agendas relevant kept implemented by Indonesia consistently in organizing the ASEM Interfaith Dialogue in Indonesia, Cyprus, China, the Netherlands and South Korea.